Adsorção de atrazina em biocarvões obtidos a partir de colmo de bambu - Sbizzaro, Mariana (2016)
The agricultural sector has great influence in Brazilian economy. Furthermore, agricultural yield has been associated with pesticides application during crop cycle, which atrazine is applied for example, since it can cause environmental contamination when it does not reach its target. Thus, there are some essential and imperative options that can minimize contamination and negative impacts during agricultural practices. So, present study aimed at evaluating the ability of three biochars in atrazine adsorption. Therefore, three biochars produced from bamboo culm were used, whose species is Phyllostachys aurea, and temperature ranged at 350 ºC, 450 ºC and 550 ºC. The three studied biochars were named as BE350, BE450 and BE550. They were characterized based on their physical and chemical properties by elemental analysis, characterization of functional groups (Infrared Spectroscopy Fourier Transform - FTIR), surfaces morphology evaluation (Scanning Electron Microscopy - SEM) as well as specific surface area (ASEBET) and porosity. A kinetic study was carried out to determine the equilibrium period of adsorption process and the kinetic mechanism that controls such process. Langmuir and Freundlich isotherms were also modeled during this trial. Atrazine determination, after the adsorption test, was carried out by High Performance Liquid Chromatography (HPLC). The obtained analyses showed that the adsorption capacity of biochars decreased in the following order: BE 450> BE 350 > BE 550, and such capacity has been associated with the physical and chemical characteristics of biochars. The three studied biochars are well represented by the kinetic model of pseudo-second order. At last, all biochars have shown high affinity to adsorb atrazine; however, the biochar that was produced at 450 ºC has shown the highest adsorption capacity.